Water wave diffraction and the spectral response surface method - Walker, D; Taylor, P; Taylor, R; Tromans, P; Zang, J (2007)
For the purposes of guiding air-gap design, wave-structure interaction is modelled using linear and 2nd-order diffraction theory. A 4-column gravity-based structure is considered, consisting of a subsurface caisson with 4 large-diameter columns mounted on top. The diffraction analyses are combined with the spectral response surface (SRS) method of Tromans and Vanderschuren to compute extreme surface elevation statistics. Water is predicted to reach very high elevations both close to the columns and at the geometric center of the structure. Comparisons with real wave data are made and conclusions on the ability of this approach to reproduce real wave measurements beneath a gravity-based structure are discussed. Copyright © by The International Society of Offshore and Polar Engineers.